(untitled) (Proceedings of Southern Federal University. Philology, 2014)
The article is devoted to the analysis of language reflection in metropolitan Veniamin Fedchenkov’ diaries. The focus is given to the linguistic means, which he uses to describe some events. The author studies different ways of word meaning actualization according to the morpheme meaning. Keywords: diary, linguistic reflection, word meaning actualization, morpheme. Author: Panova A.A.